Exchange Rate Analysis in Support of IMF Surveillance : A Collection of Empirical Studies - Tsangarides, Charalambos (International Monetary Fund, 2008)
Exchange rate analysis lies at the center of the IMF's surveillance mandate and policy advice, as well as in the design of IMF-supported programs, and IMF staff are called upon to analyze a wide variety of exchange rate issues in various member countries, both small and large, from the least economically developed to the most advanced, and from those whose currencies circulate only locally to those whose currencies are of global importance. Each year, IMF staff produce dozens of studies on exchange rate issues, some published by the IMF, others in various professional journals or books. This book aims to give a flavor of the topics the IMF staff typically examine under the broad rubric of exchange rate analysis, encompassing several topics: determination and impact of the real exchange rate, assessing competitiveness and the equilibrium real exchange rate in specific countries or country groups, and considerations in the choice of exchange rate regime.